Memanggil Arwah Leluhur dalam Legenda Arjowilangun: Kajian Etnobotani Tumbuhan Ritual pada Tradisi Leang-Leong - Syarifatun Nafisah; Khofifah Dwi Rahmawati; Safinatin Najah; Dwi Ainun Najah; Fahrul Ghani Muhaimin; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to document and preserve the local knowledge of the Arjowilangun community, in Malang Regency, East Java, regarding the use of plants in the Leang-Leong tradition. The methodology employed is qualitative descriptive, with data collection techniques including interviews with key informants identified through purposive sampling (traditional leaders), as well as additional informants identified through snowball sampling. Observations were conducted to verify the use of plants in the Leang-Leong ritual, and document analysis was used to support secondary data. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate that there are 14 plant species from 11 families utilised in the Leang-Leong tradition. Kembang setaman is the most commonly used plant species. Each plant holds a distinct philosophical meaning, reflecting the rationale for its use in each ritual. The conservation status of most plants is classified as Least Concern, indicating that their populations remain stable, although community conservation efforts have not yet been fully optimised. The utilisation of various plants within this tradition reflects the close relationship between humans and nature.